The activities of the Russian-Ukrainian-Polish commission on repatriation in 1921–1924 - Borovskaya, Olga N. (Journal of the Belarusian State University. International Relations, 2023)
The article considers the work of the Mixed Russian-Ukrainian-Polish commission on repatriation in 1921–1924 and the issues affecting its effectiveness. The commission’s performance was highly dependent on the state of Soviet-Polish relations at the time. Soviet Russia and Poland established diplomatic relations, but the bilateral ties remained tense, and these tensions impeded the overall progress of repatriation. It is shown that especially during the Riga peace conference (September 1920 – March 1921), the return of the prisoners of war and other nationals was recognised as an acute problem, and art. VII of the Preliminary peace treaty of 12 October 1920, envisaged the creation of mixed commissions. Immediately, the Polish side asked for the return of the prisoners of war, but the Russian-Ukrainian delegation insisted that it could proceed only if the truce was extended, which the Polish side refused to do. It is emphasised that from the beginning, the Polish side was reluctant to address the most contentious questions via the Russian-Ukrainian-Polish commission on repatriation. Disputes erupted over the exchange of individuals, which the parties had committed to performing as a priority under the additional protocol of understanding of 24 February 1921. The article details the cooperation between the Mixed commission on repatriation and the relevant bodies on improving the material and sanitary conditions of the repatriates, notably, between the branches of the Red Cross Society and the Central directorate for the evacuation of the population of the RSFSR, with a focus on the division of the Mixed commission on reparation for the western region, which covered the Vitebsk, Gomel and Smolensk provinces of the RSFSR and the BSSR. It is also shown that the Polish delegation of the Mixed commission on reparation was de facto providing consular services to the Polish nationals in the western regions and the BSSR. It has been established that the initiative to close the process of repatriation of prisoners of war and refugees came from the Soviet side, and responded to the decrease in the numbers willing to repatriate en masse (“in echelon order”, i. e. by evacuation trains). On 15 February 1923, the Russian-Ukrainian delegation to the Mixed commission on repatriation announced its return and the suspension of the evacuation trains. The Polish side was offered to take similar action and deal with any future matters concerning repatriation by diplomacy. The Polish government suggested that the mandate of the repatriation commission be extended until 1 February 1924, and those of its divisions (in Kyiv, Kharkiv and Minsk) until 15 January 1924. The final protocol ending the mandate of the Mixed commission on repatriation was not signed until 30 August 1924. The repatriation process and the work of the commission were declared complete on 1 September 1924. The Polish delegation referred all unfinished repatriation cases to the consular department of its diplomatic mission. The following estimates are given for the numbers of repatriates who returned to their home countries during the mass repatriation period in 1921–1925: the Republic of Poland (over 1.5 mln, including 1.1–1.2 thnd returning independently), and the USSR (1.2 mln).
Keywords: repatriation; Russian-Ukrainian-Polish commission on repatriation; Tsentrevak of the RSFSR; prisoners of war; refugees